Prevalence and exploration of factors associated with instrumental activities of daily living disability among elderly in Kelantan : a mixed-methods study - Ismail, Nur Raihan (2022)
Background: Population ageing has been associated with as a higher burden of diseases, injury and chronic illness in which contributes to the higher disability rates. The development of disability in old age is regarded as a dynamic social phenomenon that relates to individual physiological, health conditions, socio-economic position as well as environment in which people live. Instrumental activities of daily living (IADL) is a construct which describes the functional ability to perform complex activities. Studies on IADL in Malaysia are still lacking. Objective: This study aimed to determine the factors associated with, and further explain how these factors contribute to IADL disability among elderly attending health clinics in Kelantan. Methodology: This was a mixed-methods study, with sequential explanatory design conducted between January 2020 to August 2021. The two-phase design began with a quantitative cross-sectional health survey, followed by qualitative interviews using phenomenology approach. The survey study identified the disabled IADL status and the related factors using Lawton IADL scale, Elderly Cognitive Assessment Questionnaire (ECAQ), Geriatric Depression Scale (GDS) and Duke Social Support Index (DSSI). This quantitative study included 248 randomly selected samples from 12 health clinics in Kelantan, Malaysia. Disabled IADL status was defined as having difficulty performing at least one out of eight activities in Lawton IADL scale. Multiple logistic regression (MLR) was performed to assess factors influencing IADL disability. The qualitative study used in-depth interview, exploring the factors associated with IADL disability among those who have disabled IADL status identified from the health survey. The 16 respondents were purposively selected, a subset from the phase one study. The interviews were transcribed per verbatim, and the data were analysed using thematic analysis. Results: Out of 248 elderly people, 36.3% of them had disabled IADL status. The factors influencing IADL disability were, age group 70 years old and above (Adj. OR 3.52; 95% CI: 1.85, 6.69, p-value<0.001), being unmarried (Adj. OR 2.37; 95% CI: 1.25, 4.49, p-value=0.008), no formal education (Adj. OR 4.03; 95% CI: 1.64, 9.88, p-value=0.002), low level of income (Adj. OR 2.37; 95% CI: 1.11, 5.07, pvalue= 0.026) and those who reported fair or poor self-rated health status (Adj. OR 2.53; 95% CI: 1.31, 4.89, p-value=0.006). Five themes emerged from phase two study. These were age-related problems, social support, culture and individual character, poor educational attainment, and financial challenges. Conclusion: This study findings underlined the need to improve strategies in promoting health and wellbeing of our elderly. Policies should aim to reduce the burden of complication of chronic diseases. An equitable universal social protection policy should be available for all elderly.